Bilateral leg differences in soccer kick kinematics following exhaustive running fatigue - Katis, A.; Kellis, E.; Lees, A. (Asian Journal of Sports Medicine, 2017)
Background: Understanding fatigue effects on kicking technique with both legs would allow coaches to design soccer-specific training programs.